Magnetism and Magnetic Materials - Neeraj Panwar (IntechOpen, 2018)
The aim of the book is to provide the reader with a comprehensive overview of the current research in the interesting field of magnetism and magnetic materials. Some very interesting topics like erasing and retrieving the particular magnetic domain of a ferromagnetic thin film, the single domain behaviour of magnetic nanowire with dimension less than 100 nm, magneto-transport behaviour of Heusler alloys etc. have been covered.
English
Keywords: Physical Sciences; Engineering and Technology; Materials Science; Metals and Nonmetals; Electromagnetism